Peranan Manajemen Sarana Prasarana Dalam Proses Penguatan Pembelajaran Di Taman Pendidikan Al-Qur’an - Fadlilah, Kusnul (Civil Officium: Journal of Empirical Studies on Social Science, 2025)
This study aims to analyze the role of facilities and infrastructure management in strengthening the learning process at Nurul Khasiyah Qur'anic Learning Center (TPQ), Ponorogo District. Employing a descriptive qualitative field research approach, data were collected through interviews, observations, and documentation involving the TPQ head, teachers, and mosque caretakers. The research was conducted in Babadan Village, Ponorogo, East Java. Data analysis techniques included data reduction, presentation, and conclusion drawing. The results reveal that the facilities and infrastructure management at TPQ covers five main aspects: planning, procurement, maintenance, inventory, and disposal. Each stage operates according to educational management principles and supports effective learning. The learning process is structured through stages of planning, class organization, implementation, supervision, and continuous evaluation. These findings indicate that good governance of facilities and infrastructure significantly contributes to a conducive and structured learning environment.